Evaluating the scope of peer review in digital Forensics: insights from Norway and the U.K. - Bauge, Rune Kenneth; Ryser, Elénore; Sunde, Nina; Horsman, Graeme (Elsevier, 2025)
This paper investigates the implementation and utilisation of peer review practices in digital forensics (DF) within Norway and the U.K. Through a comprehensive survey of 113 DF practitioners and managers, we explore the extent to which peer review is integrated into DF investigations and the variations in practices between these two countries. Our findings reveal that while both Norway and the U.K. recognize the importance of peer review in ensuring the integrity and accuracy of DF work, there is a tendency to limit peer reviews to the examination of reports, rather than extending them to more thorough verification of results and methodologies. Utilising the Peer Review Hierarchy for DF as an analytical framework, our study highlights a significant gap in the depth of peer review practices, with both countries primarily focusing on lower-level reviews that are less likely to detect critical errors. The paper discusses the implications of these findings in the field of DF, emphasising the need for more robust and comprehensive peer review mechanisms to enhance the quality and reliability of digital evidence. Furthermore, we discuss the systemic and resource-related challenges that may hinder the implementation of more extensive peer review practices.
Keywords: 46 Information and Computing Sciences; 4604 Cybersecurity and Privacy; Legal & Forensic Medicine; Digital Forensic Science; Peer Review; Digital evidence; Quality assurance; Quality control